48 What kinds of spiritual and/or religious interventions for the wellbeing of people living with terminal illnesses did RCTs investigate in 2011–22? Findings from a Cochrane review, updating a previous review (Candy et al. 2012). (30th January 2023) - Vivat, Bella; Speck, Peter; Uddin, Inayah; Rohde, Gudrun; White, Nicola; Candy, Bridget; Jones, Louise; Tookman, Adrian; King, Michael
Abstract : Introduction: People with terminal illnesses may have spiritual and/or religious concerns and often value professional assistance with addressing these. It is again being increasingly recognised that, as Cicely Saunders originally argued, attending to the spiritual and/or religious needs of people approaching the end-of-life benefits their health and wellbeing overall. Aims: To explore the detail of spiritual and/or religious interventions for the wellbeing of adults with terminal illnesses in randomised controlled trials (RCTs) included in a 2011–22 Cochrane review. Methods: We systematically searched six databases (AMED, CENTRAL, CINAHL, EMBASE, MEDLINE, and PsycINFO) for RCTs of spiritual and/or religious interventions for the wellbeing of adults with terminal illnesses between 2011 and 2022. Our primary outcomes were spiritual wellbeing, psychological wellbeing, quality of life, coping, death distress, and quality of death/dying. Results: We identified 2569 citations, retrieved 98 full-texts, and included 40 studies, a much larger number and proportion than the 2012 review (40/2569 vs 5/3868). Studies were conducted globally: in Africa, the Americas, Asia, Australasia, and Europe. Interventions varied. Most involved psychotherapy (14) or life reflection (13). Five were explicitly spiritual or religious, e.g., Islamic prayer, or Buddhist chanting. Five comprised explicit spiritual/religious elements within a palliative care intervention. The remaining three investigated meditation or mindfulness. Studies also varied in their comparators, outcomes assessed, and outcome measures used. This variability between studies restricted and limited inter-study comparisons. Conclusions: Increasing numbers of RCTs in this field are being conducted internationally. However, they vary widely in the interventions they investigate, the outcomes they address, and the measures they use. Impact: This important, under-researched field is growing, with increasing numbers of RCTs investigating spiritual and/or religious interventions for wellbeing. However, studies are highly diverse, and, while variation is to be expected in a developing field, too much prevents comparisons of study findings. More consistency of design would enable more inter-study comparability. References: Candy B, Jones L, Varagunam M, Speck P, Tookman A, King M. Spiritual and religious interventions for well-being of adults in the terminal phase of disease. Cochrane Database of Systematic Reviews 2012;(5). Art. No.: CD007544. DOI: 10.1002/14651858.CD007544.pub2. Clark D. (2018). Cicely Saunders: a life and legacy. Oxford, England: Oxford University Press. Saunders CM. (1981). The founding philosophy. p. 4 in Saunders CM, Summers DH, Teller N (eds.), Hospice: The Living Idea. London: Edward Arnold. Knaul FM, et al, on behalf of the Lancet Commission on Palliative Care and Pain Relief Study Group. Alleviating the access abyss in palliative care and pain relief – an imperative of universal health care: the Lancet Commission report. Lancet 2018;391 :1391–454. Radbruch L, et al . Redefining palliative care – a new consensus-based definition. Journal of Pain and Symptom Management 2020;60 (4):754–64.